The Effectiveness of The Constructivist Learning Model Using Children Learning In Science (CLIS) Type in Improving Science Learning Outcomes - Sari, Dwi Resmi Novita; Wardani, Sri; Mulawarman, Mulawarman (Journal of Primary Education, 2020)
In primary schools, students are given lessons that can be used to develop their character and various potentials, one of them is science subjects. The CLIS model can be used as an alternative learning model in teaching science because it contains constructivist learning elements that lead to meaningful learning. The purpose of this study was to analyze the effectiveness of the constructivist learning model using Children Learning In Science (CLIS) type in improving student learning outcomes. This study used a quasi-experimental method. The sample was taken using a random cluster technique were students of grade V SDN 2 Patikraja as the control class and students of grade V SDN 1 Notog as the experimental class. The data analysis used was a one-sample proportion test, N-Gain analysis, and independent-sample t-test. The results show that the use of the CLIS constructivist learning model is effective in improving student learning outcomes compared to learning with the expository method. This is evidenced by the increase in student scores before and after the implementation of the CLIS constructivist learning model is in the medium category, students in experimental class achieve classical completeness >75%, and the average learning outcomes of the experimental class is higher than the control class, as well as students shows positive responses. So this research can be helpful for the students and the teachers in learning sains.